On the stabilization of the motion of uncertain affine systems - Martynyuk, A.A.; Chernetskaya, L.N.; Martynyuk-Chernienko, Yu.A. (Reports of the National Academy of Sciences of Ukraine, 2019)
The article discusses affine systems with uncertain parameter values, for the stabilization of which the linear control is applied. The study of the stability and boundedness of the motion is carried out by the direct Lyapunov method. The concept of a pair of nonlinearly stabilized systems is introduced, and the sufficient conditions for the stability and boundedness of the motion are established, including the case of stability over a finite time in terval.